Applying the regularized derivatives approach in Euler deconvolution and modeling geophysical data to estimate the deep active structures for the northern Red Sea Rift region, Egypt - SALEH, Salah; PAŠTEKA, Roman (Contributions to Geophysics and Geodesy, 2012)
The Red Sea is considered to be a typical example of a newly formed ocean.Moreover the northern Red Sea region and Gulf of Suez are generally important due totheir hydrocarbon resources. Estimation of higher derivatives of potential fields representsa significant role in geophysical interpretation (qualitative and/or quantitative), as hasbeen demonstrated in many approaches. One of the most popular methods, employinghigher derivatives is the well known Euler deconvolution method. In this method it isvery important to stabilize the derivatives evaluation, because they are very sensitive tonoise and errors in the interpreted field. One way to stabilize higher derivative evaluationis the utilization of the Tikhonov regularization. We show the influence of regularizedderivatives on the properties of the classical 3D Euler deconvolution algorithm and applyit to geophysical potential field data from the Red Sea Rift and its surroundings. Thesolution obtained with regularized derivatives gives better focused depth-estimates, whichare closer to the real position of sources; the results presented here can be used to constraindepth to active crustal structures (boundaries and volcanisms) for northern Red Sea rift.Estimated Euler solution map from Bouguer data utilizing the Tikhonov regularizationreveals both the continental-oceanic crust boundary and several shallow listric normalfaults spreading on the Red Sea margins having NW–SE direction, suggesting NE–SWextension in these regions. Also, generalized depth model for the structure of the Gulfof Aqaba (three pull-apart basins) was well recognized from this map. However, Eulersolutions with band pass filter of magnetic data gives best depth-estimates connectedwith the volcanic intrusive bodies (intense magmatic activity) prevalent on and aroundthe axial trough transform faults resulted from initiation of Red Sea Rift. This depthestimation was derived resulting different structural indexes (SI).